Aphids and their natural enemies in vegetable agroecosystems in Benin - Sæthre, May-Guri; Godonou, I.; Hofsvang, T.; Tepa-Yotto, Ghislain T.; James, B. (Springer, 2011)
his study was undertaken to provide new knowledge on biodiversity of aphids and their complex of natural enemies in vegetable agroecosystems in Benin. During a 2-year survey (2007/2008 to 2008/2009), aphid species, their host plants and natural enemies were identified from samples collected from 29 vegetable and 22 weed species at 30 vegetable production sites across Benin. A total of 82% of the vegetable species and 12% of the weed species were infested with aphids. Aphis gossypii Glover infested a wide range of the vegetables and occurred on 62% of the species, while Aphis craccivora Koch, Aphis spiraecola Patch, Lipaphis erysimi (Kalt.), Myzus persicae (Sulzer) and Toxoptera odinae (Van de Goot) were collected from a limited number of vegetables, each with a frequency occurrence ranging from 3 to 28%. The weeds Commelina benghalensis L. and Euphorbia hirta L. were common alternative weed hosts for aphids. Common natural enemies were the predators Cheilomenes propinqua (Mulsant), Cheilomenes sulphurea (Olivier) and Ischiodon aegyptius (Wiedemann), the obligate entomopathogen Neozygites sp., and the parasitoids Lysiphlebus testaceipes (Cresson) and Aphelinus ficusae Prinsloo & Neser. Lysiphlebus testaceipes was usually the only primary parasitoid on aphids across the sites and its common host was A. gossypii. From parasitized mummies, five species of hyperparasitoids were collected, the most abundant being Syrphophagus africanus (Gahan). These are the first records of L. testaceipes, S. africanus and A. spiraecola from West Africa. These findings provide baseline knowledge on the aphid fauna of Benin and contribute information for use in the development of sustainable vegetable pest management strategies in the country.